Dynamic metabolomic changes in Pochonia chlamydosporia’s parasitism of Parascaris equorum eggs - Luyao Hao; Fengmiao Zhao; Hongyou Liu; Chengyu Ma; Yuan Ma; Zhengyi Li; Wei Wei; Rui Wang (Biological Control, 2025)
Pochonia chlamydosporia, a nematophagous fungus, holds great promise as a biological control agent against animal − parasitic nematodes. However, the molecular and cellular mechanisms of its infection process remain largely unclear. In this study, metabolomics was utilized to investigate the dynamic changes in the exometabolome during the infection of P. chlamydosporia on Parascaris equorum eggs. Three crucial infection stages were selected: early (A1), middle (B1), and late (C1), with control groups of P. chlamydosporia hyphae cultured without eggs (A, B, C). Metabolite extraction was carried out, followed by Liquid Chromatography-Tandem Mass Spectrometry (LC − MS/MS) analysis to identify differentially accumulated metabolites. LC-MS/MS analysis identified 1,185 fungal-derived metabolites, with key players including Ascochalasin (membrane disruptor), Piperine (signal transducer), and 6-methoxygossypol (egg development inhibitor). These metabolites orchestrated dynamic processes: organic acids fueled TCA cycle energy supply during mid-stage infection, sphingolipids mediated membrane fusion in late stages, and alkaloids disrupted host membrane permeability. Pathway analysis revealed stage-specific hubs: alanine-aspartate metabolism dominated early infection for nitrogen acquisition, cAMP signaling peaked in mid-stage to hijack host pathways, and secondary bile acid biosynthesis surged late-stage to degrade eggshells. These findings clarify that P. chlamydosporia coordinates a metabolic cascade—from energy reprogramming to host defense evasion—to complete parasitism, providing novel targets for biocontrol agent development.